Geologi Dan Mineralisasi Endapan Emas Orogenik Di Gunung Lipan, Kecamatan Rorowatu, Kabupaten Bombana, Sulawesi Tenggara, Indonesia - Hidayatullah Hidayatullah; Arifudin Idrus; Anastasia Dewi Titisari (Jurnal Geomine, 2022)
The prospect of Gunung Lipan is located in Rorowatu District, Bombana Regency, Southeast Sulawesi Province.  Physiographically it is situated in the Rumbia mountains, which is occupied by the metamorphic rocks of Pompageo complex. The Gunung Lipan is a prospect which has potential to produce gold mineralization in the Rumbia Mountains. However, a detailed research has never been carried out, in which the latest research is still on regional scale. Therefore, this study aims to understand more details about the geological conditions, alteration types and mineralization characteristics of the prospect and its surroundings. The research methods include geological mapping, petrographic analysis to determine type of hostrock, ore microscopy analysis to determine sulfide minerals in rocks/veins, and ore geochemistry to determine metal content in rocks and veins. Gold mineralization in the Gunung Lipan is hosted by mica schist, and controlled by sinistral shear fault in form of shear zone. The fault movement in the field is indicated by the presence of a milonite structure in the rock and the texture of mica fish on microscopic observations. The hydrothermal alteration appears at the study area is a typical type of alteration found in orogenic gold deposits such as silicification, carbonatization, and carbonization, argillic and propylitic. The sulfide minerals of orogenic type of gold deposit occurred in this study consist of stibnite, sinnabar, tripuhyite, pyrite, arsenopyrite, and hematite. Sulphide minerals are present in rocks and veins in disseminated form. Based on the results of geochemical analysis of gold content ranging from 0.005 ppm to 1.25 ppm, high grade gold was found in quartz veins that cross-cut foliation and veins with brecciated texture. Correlation of metallic elements using multivariate statistical methods shows that gold is positively correlated with As, Sb, and Hg, negatively correlated with Ag, and base metal elements (Pb, Zn, and Cu) are not abundant and are depleted when there is an increase in degree of metamorphism, which obviously implies a typical characteristics of orogenic gold deposit.